Haplomacrobiotus utahensis new species of Calohypsibiidae (Eutardigrada) from North America - Pilato, Giovanni; Beasley, Clark (Zootaxa, 2005)
Haplomacrobiotus utahensis is a new species of eutardigrade from North America (Utah). It differs from H. hermosillensis in having more evident peribuccal lobes, wider buccal tube, first macroplacoid different in shape, thinner and shorter claws.